Greedy reduction of Bacillus subtilis genome yields emergent phenotypes of high resistance to a DNA damaging agent and low evolvability. Issue 6 (15th March 2023) - Dervyn, Etienne; Planson, Anne-Gaëlle; Tanaka, Kosei; Chubukov, Victor; Guérin, Cyprien; Derozier, Sandra; Lecointe, François; Sauer, Uwe; Yoshida, Ken-Ichi; Nicolas, Pierre; Noirot, Philippe; Jules, Matthieu
Abstract: Genome-scale engineering enables rational removal of dispensable genes in chassis genomes. Deviating from this approach, we applied greedy accumulation of deletions of large dispensable regions in the Bacillus subtilis genome, yielding a library of 298 strains with genomes reduced up to 1.48 Mb in size. High‐throughput physiological phenotyping of these strains confirmed that genome reduction is associated with substantial loss of cell fitness and accumulation of synthetic-sick interactions. Transcriptome analysis indicated that <15% of the genes conserved in our genome-reduced strains exhibited a twofold or higher differential expression and revealed a thiol-oxidative stress response. Most transcriptional changes can be explained by loss of known functions and by aberrant transcription at deletion boundaries. Genome-reduced strains exhibited striking new phenotypes relative to wild type, including a very high resistance (increased >300-fold) to the DNA-damaging agent mitomycin C and a very low spontaneous mutagenesis (reduced 100-fold). Adaptive laboratory evolution failed to restore cell fitness, except when coupled with a synthetic increase of the mutation rate, confirming low evolvability. Although mechanisms underlying this emergent phenotype are not understood, we propose that low evolvability can be leveraged in an engineering strategy coupling reductive cycles with evolutive cycles under induced mutagenesis.